Energy Pricing Policy and Environmental Quality in Nigeria: A Dynamic CGE Approach - Akınyemi, Opeyemi; Alege, Philip. O.; Ajayi, Oluseyi. O.; Okodua, Henry (International Journal of Energy Economics and Policy, 2017)
The fuel subsidy policy as a policy had been argued to hamper efforts at environmental sustainability. Thus, this study investigates the extent to which the removal of fuel subsidy influences the level of carbon emissions in Nigeria over a 5 year period. It adopts the recursive dynamic version of the PEP Computable General Equilibrium (CGE) model based on the 2006 Nigerian Social Accounting Matrix (SAM). Simulating a partial, gradual and complete removal of import tariff on imported petrol indicates reduction of emissions only when subsidy removal was partial. Findings from the results showed carbon emissions marginally increased under the gradual and one shot removal. This suggests that removing petrol subsidy was not sufficient to reduce carbon emissions level, but should be accompanied with necessary supporting policies. Fuel blending can be a useful alternative to fossil fuel along with renewable energy and green growth practices to ensure a low-carbon growth strategy. Keywords: Energy policy, Environmental Quality, Dynamic CGE JEL Classifications: C68, Q43, Q56